Plasmid stabilization by cell killing - Weaver, Keith (Henry Stewart Talks, 2008)
Introduction to post-segregational killing systems, Proteic post-segregational killing systems, The Ccd system, Other proteic systems, Antisense RNA-regulated post-segregational killing systems, The plasmid R1 hok/sok system, The plasmid pAD1 par system